2013
DOI: 10.3389/fnbeh.2013.00001
|View full text |Cite
|
Sign up to set email alerts
|

Enriched childhood experiences moderate age-related motor and cognitive decline

Abstract: Aging is associated with deterioration of skilled manual movement. Specifically, aging corresponds with increased reaction time, greater movement duration, segmentation of movement, increased movement variability, and reduced ability to adapt to external forces and inhibit previously learned sequences. Moreover, it is thought that decreased lateralization of neural function in older adults may point to increased neural recruitment as a compensatory response to deterioration of key frontal and intra-hemispheric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
118
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(128 citation statements)
references
References 57 publications
9
118
1
Order By: Relevance
“…This finding fits with a number of previous reports suggesting a link between musical training and response speed (e.g. expert musicians: Amer et al, 2013;older adults;Khemthong et al, 2012;Amer et al, 2013;Metzler et al, 2013;amateur musicians: Hughes & Franz, 2007;Jentzsch et al, 2014). Importantly, despite these general group differences, musicians did not differ from non-musicians in their ability to selectively prepare a forthcoming movement using pre-specified movement information or to re-program in incorrectly pre-specified motor plan.…”
Section: Discussionsupporting
confidence: 76%
“…This finding fits with a number of previous reports suggesting a link between musical training and response speed (e.g. expert musicians: Amer et al, 2013;older adults;Khemthong et al, 2012;Amer et al, 2013;Metzler et al, 2013;amateur musicians: Hughes & Franz, 2007;Jentzsch et al, 2014). Importantly, despite these general group differences, musicians did not differ from non-musicians in their ability to selectively prepare a forthcoming movement using pre-specified movement information or to re-program in incorrectly pre-specified motor plan.…”
Section: Discussionsupporting
confidence: 76%
“…optimism) or engaging in active coping mechanisms (e.g. humor, mindfulness; Wu et al, 2013) – a process that has been associated with striatum function during aversive learning (Delgado et al, 2009; Ledoux and Gorman, 2001). We observed that participants with higher self-reported resiliency (Connor-Davidson Resiliency scale; Connor and Davidson, 2003) exhibited greater activity in the right caudate ROI – defined by the contrast of positive and neutral memory recall – during the recall of positive autobiographical memories (correlation between resilience scores and parameter estimates from the right caudate ROI: r(19) = 0.458, p = .05).…”
Section: Resultsmentioning
confidence: 99%
“…Actions that are possible at one moment may not be possible a short time later. We consider these time-varying possibilities for action as dynamic affordances (see also Fajen, 2013). This contrasts with static affordances in which the timing of movement has no impact on either judging or acting on the affordance (e.g., judging the reachability of an object on a shelf).…”
mentioning
confidence: 99%